Conductive paste, current collector, secondary battery, battery module, battery pack, and electric device

CN123017981APending Publication Date: 2026-10-30CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611101455.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-07-01
Publication Date
2026-10-30

AI Technical Summary

Benefits of technology

[0008]本申请通过在导电浆料中加入固化剂,固化剂与粘结剂发生交联反应,使得部分粘结剂分子链由线性变为更牢固的三维网络结构,由此提升了部分粘结剂分子的耐溶剂性、特别是耐水性溶剂性,确保了由该导电浆料形成的涂层在集流体上的结构完整性与高粘结力,并且能保持良好的导电性,提升二次电池运行的稳定性以及循环寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017981A_ABST
    Figure CN123017981A_ABST
Patent Text Reader

Abstract

The application provides a conductive paste, a current collector, a secondary battery, a battery module, a battery pack and a power utilization device. The conductive paste comprises the following raw material components: an aqueous binder, a conductive agent, a dispersing agent and a curing agent, wherein the aqueous binder comprises an aqueous polymer with a polycarboxyl functional group, and the curing agent is used for cross-linking reaction with the aqueous polymer with the polycarboxyl functional group. The conductive paste in the embodiment of the application has good conductivity and bonding performance, and has good water resistance, so that the stability of the secondary battery during operation can be improved, and the cycle life of the secondary battery can be prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application based on the invention with application number 202280009637.X, application date July 1, 2022, applicant CATL, and invention title "Conductive slurry, current collector, secondary battery, battery module, battery pack and power supply device". Technical Field

[0002] This application relates to the field of lithium battery technology, and in particular to a conductive paste, current collector, secondary battery, battery module, battery pack and electrical device. Background Technology

[0003] Lithium-ion batteries are widely used in electronic devices such as mobile phones, tablets, laptops, wind turbines, and solar power plants due to their advantages such as high energy density, long cycle life, and low environmental pollution.

[0004] The electrode sheet of a lithium-ion battery mainly consists of an active material layer and a current collector. The bonding performance between the active material layer and the current collector affects the cycle life of the electrode sheet, while the conductivity between the active material layer and the current collector relates to the battery's electrical performance and cycle performance. Therefore, the above-mentioned issues are also one of the key research focuses in this field. Summary of the Invention

[0005] This application is made in view of the above-mentioned problems, and its purpose is to provide a conductive paste that can enhance the conductivity and adhesion between the current collector and the conductive coating, and has good water resistance, thereby improving the stability of the secondary battery during operation and extending its cycle life.

[0006] To achieve the above objectives, this application provides a conductive paste, a current collector, a secondary battery, a battery module, a battery pack, and an electrical device.

[0007] The first aspect of this application provides a conductive paste comprising the following raw material components: an aqueous binder including an aqueous polymer having polycarboxylic functionalities, a conductive agent, a dispersant, and a curing agent, wherein the curing agent is used for crosslinking reaction with the aqueous polymer having polycarboxylic functionalities.

[0008] This application introduces a curing agent into a conductive slurry. The curing agent undergoes a cross-linking reaction with the binder, causing some of the binder molecular chains to transform from linear to a more robust three-dimensional network structure. This improves the solvent resistance, especially the water resistance, of some binder molecules, ensuring the structural integrity and high adhesion of the coating formed by the conductive slurry on the current collector, while maintaining good conductivity and improving the stability and cycle life of the secondary battery.

[0009] In any embodiment, the conductive paste comprises, by weight parts: 100 parts of water-based binder, 50-150 parts of conductive agent, 800-850 parts of dispersant, and 3-16 parts of curing agent.

[0010] According to the embodiments of this application, by setting the dosage of each raw material component, the conductive paste can have good dispersibility and processability. Simultaneously, it can ensure that the water-based polymer and curing agent achieve an appropriate degree of crosslinking after the crosslinking reaction, thus forming a stable three-dimensional crosslinked network. Therefore, for the coating formed from this conductive paste, on the one hand, the conductive agent in the coating can be bound by the three-dimensional crosslinked network of the binder polymer molecules to maintain a stable and uniform dispersion state, forming a conductive network, thereby giving the coating good conductivity; on the other hand, after the electrode is immersed in the electrolyte, the coating can still maintain good adhesion properties, improving the cycle performance of the battery.

[0011] In any embodiment, the aqueous polymer having polycarboxyl functionality includes at least one of aqueous acrylic resin, ethylene-vinyl acetate copolymer, and acrylonitrile multi-component copolymer having polycarboxyl functionality.

[0012] In any embodiment, the waterborne acrylic resin comprises a copolymer of polyacrylic acid, acrylic acid, acrylates, and optionally other ethylene unsaturated monomers, or a combination thereof; optionally, the waterborne acrylic resin comprises polyacrylic acid with a number average molecular weight of 300,000 to 800,000; optionally, the acrylic acid is partially neutralized to form a salt.

[0013] Waterborne acrylic resin has good water solubility, which can ensure the wettability of conductive slurry with water, improve the spreading of waterborne cathode material slurry on the conductive coating surface and the adhesion between the cathode film and the conductive coating.

[0014] In any embodiment, the curing agent comprises a compound having two or more carboxylic acid reactive functional groups, optionally selected from at least one of aziridine, ethylene oxide, amino, and carbodiimide.

[0015] Optionally, the curing agent includes at least one of aziridine functional compounds, polycarbodiimide and its salts, epoxy-functionalized silane compounds, polymers grafted with epoxy silanes, and polyethyleneimine. Optionally, the number average molecular weight of the polycarbodiimide is 10,000 to 40,000.

[0016] According to embodiments of this application, the curing agent undergoes a crosslinking reaction with the carboxyl groups in the water-based adhesive via the reactive functional groups of carboxylic acid, forming a three-dimensional crosslinked network. The specific examples of the curing agent described above exhibit high reaction efficiency with carboxyl groups, and the resulting three-dimensional network structure possesses stable chemical properties, thereby enhancing the bonding strength between the conductive paste and the substrate.

[0017] In any embodiment, the dispersant comprises an aqueous solvent, optionally comprising water.

[0018] In any embodiment, the raw material components of the conductive paste further include a thickener, which includes at least one of xanthan gum, carboxymethyl cellulose and its salts, or poly(N-vinylacetamide).

[0019] In any embodiment, the conductive agent includes at least one of carbon black, graphite, acetylene black, Ketjen black, graphene, and carbon nanotubes.

[0020] A second aspect of this application also provides a method for preparing the conductive slurry in any of the above embodiments, the method comprising: uniformly mixing a conductive agent, a dispersant and an aqueous binder to obtain a premix; adding a curing agent to the premix and uniformly mixing to obtain the conductive slurry.

[0021] This allows the curing agent and water-based adhesive to fully cross-link and react, generating more three-dimensional network structures, improving the spreading effect of the conductive paste and its bonding strength with the substrate.

[0022] In any embodiment, the mass ratio of the curing agent to the water-based adhesive is 0.03 to 0.16. By setting a reasonable ratio, the conductive paste is guaranteed to have sufficient water resistance while also ensuring its bonding performance.

[0023] A third aspect of this application also provides a current collector, including a substrate and a conductive coating applied to the substrate, the conductive coating including a conductive agent and an aqueous polymer binder having polycarboxyl functionality, wherein the aqueous polymer is cross-linked to form a three-dimensional network structure.

[0024] In any embodiment, the conductive coating is formed by curing the conductive paste from any of the above embodiments.

[0025] In any embodiment, the substrate includes aluminum foil or an aluminum-containing polymer composite.

[0026] In any embodiment, the peel force N between the conductive coating and the substrate is ≥ 50 N / m. The adhesive incorporated in the conductive coating enhances the bond strength between the conductive coating and the substrate, thereby improving the cycle life of the secondary battery.

[0027] A fourth aspect of this application provides an electrode sheet comprising: a current collector as provided in the third aspect of this application; and an active material layer disposed on a conductive coating of the current collector.

[0028] In any embodiment, the active material layer comprises: a lithium phosphate with an olivine structure and an aqueous polymer binder.

[0029] The fifth aspect of this application provides a secondary battery, including the electrode plates of the fourth aspect of this application.

[0030] A sixth aspect of this application provides a battery module, including the secondary battery of the fifth aspect of this application.

[0031] A seventh aspect of this application provides a battery pack that includes the battery module of the sixth aspect of this application.

[0032] The eighth aspect of this application provides an electrical device including at least one selected from the fifth aspect of this application, the sixth aspect of this application, or the seventh aspect of this application.

[0033] This application introduces a curing agent into the conductive slurry. The curing agent undergoes a cross-linking reaction with the binder, causing some of the binder molecular chains to transform from linear to a more robust three-dimensional network structure. Simultaneously, the carboxyl groups, as hydrophilic groups, can better enhance the wetting, spreading, and adhesion of the active material on the conductive coating when it is subsequently coated onto the conductive coating. This ensures low resistance and high adhesion of the active material layer on the current collector, while maintaining good conductivity, thereby improving the stability and cycle life of the secondary battery. Attached Figure Description

[0034] Figure 1 This is a flowchart of one embodiment of the conductive paste preparation method according to this application. Figure 2 This is a schematic diagram of a secondary battery according to one embodiment of this application.

[0035] Figure 3 yes Figure 2 An exploded view of a secondary battery according to one embodiment of this application is shown.

[0036] Figure 4 This is a schematic diagram of a battery module according to one embodiment of this application.

[0037] Figure 5 This is a schematic diagram of a battery pack according to one embodiment of this application.

[0038] Figure 6 yes Figure 5 An exploded view of a battery pack according to one embodiment of this application is shown.

[0039] Figure 7 This is a schematic diagram of an electrical device that uses a secondary battery as a power source according to one embodiment of this application.

[0040] Figure 8 This is a cross-sectional scanning electron microscope image of an electrode sheet comprising an embodiment of this application.

[0041] Figure 9A cross-sectional scanning electron microscope image of an electrode sheet containing the conductive paste coating of Comparative Example 1 of this application.

[0042] Explanation of reference numerals in the attached figures: 1 Battery pack; 2 Upper housing; 3 Lower housing; 4 Battery module; 5 Secondary battery; 51 Housing; 52 Electrode assembly; 53 Top cover assembly; 6 Positive electrode material layer; 7 Aluminum foil; 8 Positive electrode material layer; 9 Aluminum foil. Detailed Implementation

[0043] The following detailed description, with appropriate reference to the accompanying drawings, specifically discloses embodiments of the conductive paste, current collector, secondary battery, battery module, battery pack, and power supply device of this application. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided for a full understanding of this application by those skilled in the art and are not intended to limit the subject matter of the claims.

[0044] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0045] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.

[0046] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.

[0047] Unless otherwise specified, all steps of this application may be performed sequentially or randomly, preferably sequentially. For example, if the method includes steps (a) and (b), it means that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, if the method may also include step (c), it means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0048] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0049] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0050] The positive electrode of a lithium-ion battery primarily uses aluminum foil or aluminum-containing polymer composite materials as the substrate for the current collector. In related technologies, the electrode fabrication process involves directly coating an active material slurry onto the surface of the current collector substrate to form an active material layer. When water-soluble binders are used to manufacture the active material slurry, the wettability between the current collector substrate surface and the slurry is low, resulting in limited contact area between the active material particles and the substrate, leading to poor adhesion. Consequently, the electrode resistance increases, causing a rise in the battery's internal resistance. In particular, the battery's electrical performance significantly decreases under high-rate charge-discharge conditions. Furthermore, the bonding strength of the water-soluble binder in the active material slurry is limited; during continuous charge-discharge, the active material layer easily expands and detaches from the substrate, further increasing the battery's internal resistance and affecting its cycle life and safety performance. Therefore, a conductive coating needs to be applied to the surface of the substrate to tightly bond the active material slurry to the substrate, ensuring adhesion and conductivity between the active material layer and the substrate.

[0051] In related technologies, the active material slurry of lithium battery cathodes mostly uses organic solvents, thus there are no strict requirements for the water resistance of the conductive coating on the current collector. With the development of battery technology and the demand for green environmental protection, the active material slurry of lithium battery cathodes is gradually shifting towards environmentally friendly and pollution-free formulations based on water-based solvents. However, when using water-based solvents, the conductive coating, due to insufficient water resistance, will be dissolved by the water-based solvent in the cathode active material slurry. After the conductive coating dissolves, its structure is damaged, losing its conductivity. More seriously, it can cause the active material layer to detach from the current collector substrate, leading to various abnormalities in battery performance and safety.

[0052] To address the above problems, this invention develops a water-resistant conductive paste. Applying this conductive paste to a substrate can prevent the conductive coating from dissolving in water, thus preventing the current collector from detaching from the active material layer. This ensures the normal use of the positive electrode and the safety and performance of the lithium battery.

[0053] conductive paste In a first aspect, this application provides a conductive paste comprising the following raw material components: an aqueous binder including an aqueous polymer having polycarboxylic functionalities, a conductive agent, a dispersant, and a curing agent, wherein the curing agent is used for crosslinking reaction with the aqueous polymer having polycarboxylic functionalities.

[0054] In this embodiment, the water-based adhesive is a water-soluble adhesive with advantages such as being non-polluting, highly flame-retardant, and having good conductivity, making it suitable for use in conductive layers. By using a water-based polymer with multiple carboxyl functional groups as the water-based adhesive, the carboxyl groups can improve the water solubility of the adhesive, and they also have good reactivity, allowing them to react with other substances and change their properties.

[0055] Curing agents are substances that control the curing reaction and are used to improve the water resistance of some adhesives. Specifically, some groups in the curing agent can undergo a cross-linking reaction with the carboxyl groups in the water-based adhesive, transforming the two-dimensional carboxyl molecular chains into a more robust three-dimensional network structure. This three-dimensional network structure not only improves the water resistance of the water-based adhesive but also enhances the stability of its structure and improves its adhesion.

[0056] Conductive agents are materials with good electrical conductivity. Adding conductive agents can improve the conductivity of conductive adhesives and ensure the conduction of electrical energy between the active material layer and the current collector substrate. Dispersants can improve the dispersion performance of various raw materials in water-based binders and ensure the performance stability of conductive slurries.

[0057] This application introduces a curing agent into a conductive slurry. The curing agent undergoes a cross-linking reaction with the binder, causing some of the binder molecular chains to transform from linear to a more robust three-dimensional network structure. This improves the solvent resistance, especially the water resistance, of some binder molecules, ensuring the structural integrity and high adhesion of the coating formed by the conductive slurry on the current collector, while maintaining good conductivity and improving the stability and cycle life of the secondary battery.

[0058] In some embodiments, the conductive paste comprises, by weight, 100 parts of water-based binder, 50-150 parts of conductive agent, 800-850 parts of dispersant, and 3-16 parts of curing agent.

[0059] In the embodiments of this application, the dispersant can be an aqueous solvent. Optionally, deionized water can be used as the dispersant. The aforementioned dispersants are readily available and have low material costs. Further, the amount of dispersant added is 800-850 parts. It is understood that if the amount of dispersant added is less than 800 parts, the viscosity of the conductive paste is high, and the mixing efficiency is low. When the amount of dispersant is greater than 850 parts, it increases the drying and curing time of the subsequent conductive paste layer, reducing the efficiency of conductive coating preparation. Therefore, the aforementioned amount of dispersant added can improve the preparation efficiency of the conductive coating.

[0060] In this embodiment, the amount of conductive agent added is 50 to 150 parts. When the amount of conductive agent added is less than 50 parts, the conductivity is insufficient, which will affect the electrical energy conduction between the active material layer and the current collector substrate, reducing the battery's electrical performance. When the amount of conductive agent added is greater than 150 parts, it will increase the mass of the electrode sheet and reduce the energy density of the secondary battery. Therefore, the above-mentioned amount of conductive agent added can ensure both the electrical performance and energy density of the secondary battery.

[0061] In this embodiment, 100 parts of water-based binder and 3-16 parts of curing agent are added. Adding sufficient water-based binder ensures the bonding performance of the conductive paste. The amount of curing agent added is less than that of the water-based binder; it is used to undergo a crosslinking reaction with a portion of the water-based binder, transforming some of the two-dimensional carboxyl molecular chains into three-dimensional network structure molecules, thus improving the water resistance of the water-based binder. The remaining portion of the water-based binder does not participate in the crosslinking reaction and still maintains its own bonding performance, ensuring the adhesion of the conductive paste and improving the bonding strength between the active material layer and the current collector substrate.

[0062] In this application's technical solution, by setting reasonable raw material components and their appropriate dosages, the conductive slurry can achieve good dispersibility and processability. Simultaneously, it ensures that the water-based polymer and curing agent achieve an appropriate degree of crosslinking after the crosslinking reaction, forming a stable three-dimensional crosslinked network. Therefore, for the coating formed from this conductive slurry, on the one hand, the conductive agent in the coating can be bound by the three-dimensional crosslinked network of the binder polymer molecules, maintaining a stable and uniform dispersion to form a conductive network, thus giving the coating good conductivity; on the other hand, after the electrode is immersed in the electrolyte, the coating can still maintain good adhesion, improving the battery's cycle performance.

[0063] In some embodiments, the aqueous polymer having polycarboxyl functionality includes at least one of aqueous acrylic resin, ethylene-vinyl acetate copolymer, and acrylonitrile multi-component copolymer having polycarboxyl functionality, optionally including polyacrylic acid, wherein the molecular weight of the polyacrylic acid is 300,000 to 800,000.

[0064] Waterborne acrylic resins, ethylene-vinyl acetate copolymers, and acrylonitrile multi-component copolymers with multiple carboxyl functional groups all have multiple active carboxyl functional groups that can participate in crosslinking reactions with curing agents.

[0065] Specifically, waterborne acrylic resins include acrylic resin emulsions, aqueous dispersions of acrylic resins (also known as water-dilutable acrylic acid), and aqueous solutions of acrylic resins. They offer advantages such as low price, safe use, and environmental friendliness. Acrylic resins are a general term for polymers of acrylic acid or methacrylic acid and their derivatives. While an acrylic acid molecule or a methacrylic acid molecule contains one active carboxyl group, multiple acrylic resins, being polymers of acrylic acid or methacrylic acid and their derivatives, possess multiple active carboxyl groups. Therefore, this structure provides a sufficient number of active carboxyl groups for the curing and crosslinking reaction, ensuring its smooth progress.

[0066] Ethylene-vinyl acetate copolymer (EVA) has the molecular formula (C2H4). x (C4H6O2) y It is non-irritating. The active carboxyl groups in ethylene-vinyl acetate originate from vinyl acetate monomers, and each vinyl acetate monomer contains one active carboxyl group. Therefore, the above copolymer can provide enough active carboxyl groups to participate in the curing and crosslinking reaction. At the same time, the low molecular weight can ensure the energy density of the secondary battery.

[0067] Acrylonitrile multi-component copolymers with multiple carboxyl functional groups have multiple active carboxyl groups, which can provide enough active carboxyl groups to participate in the curing and crosslinking reaction. Furthermore, acrylonitrile multi-component copolymers have good thermal stability, which can ensure the improvement of the heat resistance of conductive pastes.

[0068] Optionally, in this embodiment, polyacrylic acid with an average molecular weight of 300,000 to 800,000 is used as a water-based binder, which is simple to prepare, has low material cost, and low toxicity. Each acrylic monomer has one active carboxyl group, therefore, polyacrylic acid with the above-mentioned molecular weight can also provide enough active carboxyl groups to participate in the curing and crosslinking reaction.

[0069] In the embodiments of this application, the above-mentioned aqueous polymers with polycarboxyl functionality can all undergo curing and crosslinking reactions with curing agents, and have stable structures and high reaction efficiency, which can effectively ensure the bonding effect of conductive pastes.

[0070] In some embodiments, the waterborne acrylic resin comprises a copolymer of acrylic acid, acrylates, and optionally other ethylene unsaturated monomers; optionally, the acrylic acid is partially neutralized to form a salt.

[0071] All of the above-mentioned substances have a certain degree of water solubility, which can ensure the solubility of conductive paste in water-based solvents.

[0072] In some embodiments, the curing agent comprises a compound having two or more carboxylic acid reactive functional groups, optionally selected from at least one of aziridine, ethylene oxide, amino, and carbodiimide. Optionally, the curing agent includes at least one of aziridine functional compounds, polycarbodiimide and its salts, epoxy-functionalized silane compounds, polymers grafted with epoxy silanes, and polyethyleneimine. Optionally, the molecular weight of the polycarbodiimide is 10,000 to 40,000.

[0073] When aziridine functional compounds are selected as curing agents, the carboxyl groups in the water-based adhesive and the aziridine groups in the aziridine functional compounds can undergo a good cross-linking reaction at room temperature, which can produce a three-dimensional network structure and improve the water resistance of the conductive paste.

[0074] When polycarbodiimide and its salts are selected as curing agents, the carbodiimide and carboxyl groups undergo cross-linking reactions to form a three-dimensional network structure. Furthermore, the above structure exhibits better dispersion performance in aqueous solvents, ensuring the water resistance of the conductive paste while improving the uniformity of binder dispersion in the conductive paste.

[0075] When epoxy-functionalized silane compounds or grafted epoxy silanes are selected as curing agents, the epoxy groups react with the carboxyl groups to introduce hydrolyzable silane groups. Then, through the hydrolysis and condensation of silane groups, Si-O-Si crosslinks are formed to obtain a three-dimensional network structure, thereby improving the water resistance of the conductive paste.

[0076] When polyethyleneimine is used as a curing agent, the epoxy groups and carboxyl groups react to produce a three-dimensional network structure, which improves the water resistance of the conductive paste.

[0077] The reactive functional group of carboxylic acid can undergo cross-linking reaction with the carboxyl group in water-based adhesives. The above-mentioned materials have high reaction efficiency with carboxyl groups, and the resulting three-dimensional network structure has stable chemical properties, which can enhance the bonding strength between conductive paste and matrix.

[0078] In some embodiments, the dispersant includes an aqueous solvent, and optionally, the aqueous solvent includes water.

[0079] Using water as a dispersant is inexpensive, readily available, and provides good dispersion.

[0080] In some embodiments, the raw material components of the conductive paste also include a thickener, which includes at least one of xanthan gum, carboxymethyl cellulose and its salts, or poly(N-vinylacetamide).

[0081] By selecting the above-mentioned thickeners, not only can the rheological properties of the conductive slurry be adjusted to achieve the thickening effect, but the conductive agent can also be dispersed by the steric hindrance effect, thus achieving some of the functions of a dispersant.

[0082] In some embodiments, the content of thickener in the raw material components of the conductive paste is 1 to 10 parts per 100 parts by weight of water-based binder.

[0083] Adding an appropriate amount of thickener, while ensuring the thickening effect and controlling the quality of the thickener, effectively guarantees the energy density of the secondary battery.

[0084] In some embodiments, the conductive agent includes at least one selected from carbon black, graphite, acetylene black, Ketjen black, graphene, and carbon nanotubes. The conductive agent is used to improve the conductivity of the positive electrode active material layer. This application does not impose specific limitations on the type of conductive agent; it can be selected according to actual needs.

[0085] Preparation method of conductive paste In a second aspect of this application, a method for preparing a conductive paste is provided for preparing the conductive paste as described in the first aspect. Figure 1 This is a flowchart of one embodiment of the conductive paste preparation method according to this application. The following will describe... Figure 1 An example of a method for preparing conductive paste is shown.

[0086] like Figure 1 As shown, the method for preparing conductive paste includes the following steps: S11. The conductive agent, dispersant and water-based binder are mixed evenly to obtain a premix; S12. Add curing agent to the premix and mix evenly to obtain conductive paste. According to an embodiment of the conductive paste preparation method of this application, a conductive agent, a dispersant, and a water-based binder are first mixed into a mixture, and then a curing agent is added to the mixture. By adding the curing agent, it can undergo a crosslinking reaction with the water-based binder, thereby improving the water resistance of the conductive paste. The above-mentioned method for preparing the conductive paste is simple and highly manufacturable.

[0087] In some embodiments, the mass ratio of the curing agent to the water-based adhesive is 0.03 to 0.16.

[0088] In the embodiments of this application, by setting the mass ratio of the curing agent to the water-based binder as described above, the crosslinking reaction between the curing agent and the water-based binder can be successfully completed, improving the water resistance of the conductive paste, while ensuring the bonding performance of the water-based binder itself, improving the connection strength between the conductive coating and the current collector substrate, and ensuring the cycle performance of the secondary battery.

[0089] current collector A third aspect of this application provides a current collector comprising a substrate and a conductive coating applied to the substrate, the conductive coating comprising a conductive agent and an aqueous polymer binder having polycarboxyl functionality, wherein the aqueous polymer is cross-linked to form a three-dimensional network structure.

[0090] In some embodiments of this application, the substrate has two surfaces opposite each other in its own thickness direction, and the conductive coating is disposed on either or both of the two opposite surfaces of the substrate.

[0091] In some embodiments of this application, the substrate may be made of metal foil or composite material sheet. For example, aluminum foil may be used as the metal foil. The composite material sheet may include a polymer material and a metal layer formed on at least one surface of the polymer material. The composite material sheet may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0092] In some embodiments of this application, the current collector described above can be used in both the positive and negative electrode sheets. When used in the positive electrode sheet, the substrate can be selected from materials suitable for the positive electrode sheet, such as aluminum foil or aluminum-containing composite material sheets. When used in the negative electrode sheet, the substrate can be selected from materials suitable for the negative electrode sheet, such as copper foil.

[0093] The conductive coating is formed by applying the conductive paste from any of the above embodiments to one or both surfaces of the substrate, followed by cold pressing and drying.

[0094] In this embodiment, the current collector, by adding a curing agent to the raw materials of the conductive slurry, undergoes a cross-linking reaction with the water-based binder. This causes some of the binder molecular chains to transform from linear to a more robust three-dimensional network structure, ensuring low resistance and high adhesion of the conductive coating on the current collector. Simultaneously, the carboxyl groups in the curing agent, as hydrophilic groups, better guarantee the wetting, spreading, and bonding effects of the water-based active material layer on the conductive slurry, improving the stability and cycle life of the secondary battery.

[0095] In some embodiments, the conductive coating is formed by curing a conductive paste as described in any of the above embodiments.

[0096] In the embodiments of this application, the aforementioned conductive paste is uniformly coated onto a substrate, and after drying and cold pressing, the current collector in the embodiments of this application is obtained. The aforementioned current collector refers to a current collector without a conductive coating. The conductive coating enhances the adhesion strength between the conductive coating and the substrate.

[0097] In some embodiments, the substrate includes aluminum foil or an aluminum-containing polymer composite.

[0098] In some embodiments of this application, a conductive coating is applied to the positive electrode sheet. In the positive electrode sheet, an aqueous solvent is used as the positive electrode active material. The conductive coating in the embodiments of this application has good hydrophilicity, allowing the aqueous solvent to effectively wet the conductive coating. Furthermore, the conductive coating in this application also possesses high water resistance, thus maintaining its original structure and not dissolving during contact with aqueous solvents. Therefore, the aforementioned conductive coating can be well applied in aqueous positive electrode active material systems.

[0099] In some embodiments, the peel force N between the conductive coating and the substrate is ≥50 N / M.

[0100] In some embodiments of this application, the conductive coating has good wettability and adhesion to the substrate, thus the conductive coating and the substrate can have high peel force.

[0101] Positive electrode sheet The fourth aspect of this application also provides a positive electrode sheet, including a current collector as described in the third aspect and a positive active material layer disposed on a conductive coating of the current collector.

[0102] In some embodiments of this application, the positive current collector has two surfaces opposite each other in its own thickness direction, and the positive active material layer is disposed on either or both of the two opposite surfaces of the positive current collector.

[0103] In some embodiments of this application, the current collector of the positive electrode may be made of aluminum foil or an aluminum-polymer composite material layer. The aluminum-polymer composite material layer may include a polymer base layer and an aluminum layer formed on at least one surface of the polymer base layer. The composite current collector may be formed by forming a metallic material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0104] In some embodiments of this application, the active material layer includes: a lithium phosphate with an olivine structure and an aqueous polymer binder.

[0105] In some embodiments, the positive electrode film may optionally include a conductive agent. As an example, the conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0106] In some embodiments, the positive electrode sheet can be prepared by dispersing the above-mentioned components for preparing the positive electrode sheet, such as positive active material, conductive agent, compound dispersant stabilizer, aqueous binder and any other components, in a solvent (e.g., deionized water) to form a positive electrode slurry; coating the positive electrode slurry onto the conductive coating of the current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0107] In some embodiments, the prepared positive electrode is an aqueous positive electrode, wherein the positive electrode active material is a lithium phosphate with an olivine structure, such as lithium iron phosphate; the binder is an aqueous polymer binder, such as a copolymer of acrylonitrile and acrylic acid; and the solvent is an aqueous solvent, such as water.

[0108] In addition, please refer to the appendix as appropriate below. Figures 2 to 7 This application describes the secondary battery, battery module, battery pack, and electrical device. Figure 2 This is a schematic diagram of a secondary battery according to one embodiment of this application. Figure 3 yes Figure 2 An exploded view of a secondary battery according to one embodiment of this application is shown. Figure 4 This is a schematic diagram of a battery module according to one embodiment of this application. Figure 5 This is a schematic diagram of a battery pack according to one embodiment of this application. Figure 6 yes Figure 5 An exploded view of a battery pack according to one embodiment of this application is shown. Figure 7 This is a schematic diagram of an electrical device that uses a secondary battery as a power source according to one embodiment of this application.

[0109] The fifth aspect of this application provides a secondary battery, including the positive electrode sheet of the fourth aspect of this application.

[0110] Typically, a secondary battery consists of a positive electrode, a negative electrode, an electrolyte, and a separator. During charging and discharging, active ions move back and forth between the positive and negative electrodes, inserting and releasing. The electrolyte acts as a conductor between the positive and negative electrodes. The separator, positioned between the positive and negative electrodes, primarily prevents short circuits while allowing ions to pass through.

[0111] In some embodiments of this application, the positive electrode may be the positive electrode described in the fourth aspect of this application. Therefore, the foregoing description of embodiments of the electrode according to this application is also applicable to the positive electrode in a secondary battery, and the same content will not be repeated.

[0112] In some embodiments of this application, the negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector, the negative electrode film layer including a negative electrode active material.

[0113] As an example, the negative electrode current collector has two surfaces opposite each other in its own thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.

[0114] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0115] In some embodiments, the negative electrode active material may be a negative electrode active material known in the art for use in batteries. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, this application is not limited to these materials, and other conventional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0116] In some embodiments, the negative electrode film layer may optionally include an adhesive. The adhesive may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0117] In some embodiments, the negative electrode film may optionally include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0118] In some embodiments, the negative electrode film may optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).

[0119] In some embodiments, the negative electrode sheet can be prepared by dispersing the above-mentioned components for preparing the negative electrode sheet, such as negative electrode active material, conductive agent, binder and any other components, in a solvent (e.g., deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto the negative electrode current collector, and obtaining the negative electrode sheet after drying, cold pressing and other processes.

[0120] In some embodiments of this application, the electrolyte acts as a conductor of ions between the positive and negative electrode plates. This application does not impose specific limitations on the type of electrolyte; it can be selected according to requirements. For example, the electrolyte can be liquid, gel-like, or entirely solid.

[0121] In some embodiments, the electrolyte is an electrolyte solution. The electrolyte solution includes an electrolyte salt and a solvent.

[0122] In some embodiments, the electrolyte salt may be selected from one or more of NaPF6, NaClO4, NaBF4, KPF6, KClO4, KBF4, LiPF6, LiClO4, LiBF4, Zn(PF6)2, Zn(ClO4)2, and Zn(BF4)2.

[0123] In some embodiments, the electrolyte salt may be selected from one or more of NaPF6, NaClO4, and NaBF4.

[0124] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.

[0125] In some embodiments, the electrolyte may optionally include additives. For example, additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature or low-temperature performance, etc.

[0126] In some embodiments of this application, there are no particular restrictions on the type of separator membrane; any known porous separator membrane with good chemical and mechanical stability can be selected.

[0127] In some embodiments, the material of the separator can be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0128] In some embodiments, the positive electrode, negative electrode, and separator can be fabricated into an electrode assembly by a winding process or a stacking process.

[0129] In some embodiments, the secondary battery may include an outer packaging. This outer packaging may be used to encapsulate the electrode assembly and electrolyte described above.

[0130] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging of the secondary battery can also be a soft pack, such as a pouch. The material of the soft pack can be plastic; examples of plastics include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0131] This application does not impose any particular limitation on the shape of the secondary battery; it can be cylindrical, square, or any other arbitrary shape. For example, Figure 2 A square-structured secondary battery 5 is shown as an example.

[0132] In some implementations, refer to Figure 3 The outer packaging may include a housing 51 and a cover 53. The housing 51 may include a base plate and side plates connected to the base plate, the base plate and side plates forming a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the cover 53 can be placed over the opening to close the receiving cavity. A positive electrode, a negative electrode, and a separator can be formed into an electrode assembly 52 using a winding or stacking process. The electrode assembly 52 is encapsulated within the receiving cavity. Electrolyte is immersed in the electrode assembly 52. ​​The secondary battery 5 may contain one or more electrode assemblies 52, which can be selected by those skilled in the art according to specific practical needs.

[0133] In some implementations, the secondary batteries can be assembled into a battery module, and the number of secondary batteries contained in the battery module can be one or more, the specific number of which can be selected by those skilled in the art according to the application and capacity of the battery module.

[0134] Figure 4 Battery module 4 is shown as an example. (See reference...) Figure 4 In battery module 4, multiple secondary batteries 5 can be arranged sequentially along the length of battery module 4. Of course, they can also be arranged in any other manner. Furthermore, these multiple secondary batteries 5 can be fixed in place using fasteners.

[0135] Optionally, the battery module 4 may also include a housing with a receiving space in which a plurality of secondary batteries 5 are received.

[0136] In some embodiments, the battery modules described above can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be one or more, the specific number of which can be selected by those skilled in the art according to the application and capacity of the battery pack.

[0137] Figure 5 and Figure 6 Battery pack 1 is shown as an example. (See reference...) Figure 5 and Figure 6 The battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box includes an upper body 2 and a lower body 3, with the upper body 2 covering the lower body 3 to form a closed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.

[0138] In addition, this application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in this application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.

[0139] As the electrical device, a secondary battery, battery module, or battery pack can be selected according to its usage requirements.

[0140] Figure 7An example electrical device is shown. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. To meet the high power and high energy density requirements of the secondary battery for this device, a battery pack or battery module can be used.

[0141] Another example device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use a rechargeable battery as their power source.

[0142] Example The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.

[0143] Examples 1-8 Preparation of positive electrode conductive paste A water-based adhesive, conductive agent, and thickener are mixed, and then a curing agent is added according to the weight ratio in Table 1 below to obtain a solid mixture. Finally, water with a solid content of 10% is added to prepare a positive electrode conductive slurry.

[0144] Specifically, the conductive agent used is conductive graphite (purchased from Shanghai Kaiyin Chemical Co., Ltd., brand name SP5000); the thickener is xanthan gum (molecular weight approximately 1,000,000 g / mol, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.); the water-based binder is polyacrylic acid with a number average molecular weight of 300,000-800,000; and the curing agent is polycarbodiimide with a number average molecular weight of 10,000-40,000.

[0145] Examples 2-7 are identical to Example 1 except for the ratio of binder to curing agent in the formulation. Example 8 uses epoxy silane as the curing agent, and is otherwise identical to Example 1.

[0146] Comparative Examples 1-5 The types and proportions of raw materials added in Comparative Examples 1 to 5 are different, but the preparation methods are the same as those in Comparative Example 1.

[0147] The relevant parameters of the conductive pastes of Examples 1-8 and Comparative Examples 1-5 are shown in Tables 1 and 2 below.

[0148] Table 1: Raw material ratio of binder to curing agent in conductive pastes of Examples 1-8 Table 2: Raw material ratio of binder to curing agent in conductive pastes of Comparative Examples 1-5 The mass fractions in Tables 1 and 2 refer to the mass content of the solid components of the corresponding raw materials in the conductive paste.

[0149] In addition, the conductive pastes obtained in Examples 1-8 and Comparative Examples 1-5 were used to prepare secondary batteries as shown below, and the performance of the secondary batteries was tested. The test results are shown in Tables 3 and 4 below.

[0150] (1) Preparation of secondary batteries 1. Preparation of positive electrode current collector 1.1 The above-mentioned positive conductive paste is uniformly coated on one surface of an aluminum foil, and then dried to obtain a positive current collector.

[0151] 1.2 Preparation of the positive electrode sheet Lithium iron phosphate (LiFePO4) positive electrode active material, conductive carbon black (conductive agent), compound dispersant and stabilizer, and aqueous binder were mixed in a weight ratio of 96:1:1.2:1.8. The compound dispersant and stabilizer was a mixture of xanthan gum (molecular weight approximately 1,000,000 g / mol, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.) and polyethyleneimine (molecular weight approximately 1200 g / mol, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.), with a weight ratio of 1:1. The aqueous binder was an acrylonitrile-acrylic acid copolymer (code LA133, purchased from Sichuan Indile Technology Co., Ltd.). The mixture was stirred and mixed evenly with deionized water to obtain a positive electrode active slurry with a solid content of 50%. The positive electrode slurry was then uniformly coated onto the positive electrode current collector conductive film layer prepared in the above steps. Following drying conditions, the positive electrode active material film layer was obtained. After cold pressing and slitting, the positive electrode sheet was obtained.

[0152] 2. Preparation of negative electrode sheet The active material artificial graphite, conductive agent carbon black, binder styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) are dissolved in deionized water at a weight ratio of 96.2:0.8:0.8:1.2 and mixed evenly to prepare a negative electrode slurry. The negative electrode slurry is uniformly coated onto the negative electrode current collector copper foil once or multiple times, and then dried, cold-pressed, and slit to obtain the negative electrode sheet.

[0153] 3. Preparation of electrolyte In an argon atmosphere glove box (H2O < 0.1 ppm, O 2<0.1ppm), mix ethylene carbonate (EC) and ethyl methyl carbonate (EMC) at a volume ratio of 3 / 7, add 12.5% ​​LiPF6 lithium salt dissolved in the organic solvent, stir well to obtain the electrolyte. 4. Separating membrane A porous PE (polyethylene) film with a 2μm thick ceramic coating is selected as the separator.

[0154] (2) Performance tests of secondary batteries 1. Interface contact angle The contact angle is the angle between the solid-liquid interface, through the liquid interior, and the gas-liquid interface at the junction of the solid, liquid, and gas phases.

[0155] In this application, the interface contact angle refers to the interface contact angle between the conductive paste on the surface of a solid material or between the dried conductive coating and water. It is an important parameter for measuring the wettability of the liquid on the solid surface and can indirectly characterize the adhesion between the liquid and the solid. By measuring the contact angle, information about the solid-liquid and solid-gas interface interactions on the material surface can be obtained. If the contact angle θ < 90°, the solid surface is hydrophilic, meaning the liquid easily wets the solid; the smaller the angle, the better the wettability. If θ > 90°, the solid surface is hydrophobic, meaning the liquid does not easily wet the solid and easily moves on the surface.

[0156] In this embodiment of the application, the Huashitong SDC-100 is used to test the interface contact angle using the droplet angle measurement method.

[0157] 2. Peeling force The conductive coating peel force test was conducted using a tensile testing machine. The machine was connected to both sides of the positive electrode sheet, and the material was pulled apart. The maximum value of the positive electrode material peeling off from the current collector was recorded. Each group was measured 5 times, and the average value was calculated after recording.

[0158] 3. Resistance After the positive electrode active material is coated onto the current collector and dried, the film resistance of the positive electrode is tested using a CRM-01 film resistance tester. Each group is tested 5 times, and the average value is taken.

[0159] 4. Battery capacity retention rate At 25°C, the batteries corresponding to each embodiment and comparative example were charged at a constant current of 1 / 3C to 3.65V, then charged at a constant voltage of 3.65V to a current of 0.05C, rested for 5 minutes, and then discharged at 1 / 3C to 2.7V. The resulting capacity was recorded as the initial capacity C0. The above steps were repeated for the same battery, and the discharge capacity Cn of the battery after the nth cycle was recorded. The battery capacity retention rate after each cycle was Pn = Cn / C0 * 100%. In this test, the first cycle corresponds to n=1, the second cycle corresponds to n=2, ..., the 100th cycle corresponds to n=100.

[0160] 5. Water resistance time Take a 5cm*5cm conductive aluminum foil with a conductive coating thickness of 2um±0.3um, completely immerse it in water, and calculate the time it takes for the coating to dissolve and expose the aluminum foil. The above time is the water resistance time.

[0161] 6. Number of cracks after cold pressing The positive electrode sheet was cold-pressed using a cold press at a pressure of 10 tons and a speed of 5 m / min, at a temperature of 20℃ to 30℃. After 24 hours of pressing, the electrode sheet was removed and observed under a scanning electron microscope. The number of surface cracks in the conductive coating within a 0.1 m² area was calculated.

[0162] In Table 1, the battery capacity retention rate data corresponding to Example 1 was obtained after 800 cycles under the above test conditions, i.e., the value of P800. The testing process for Comparative Example 1 and other examples is the same as above. The lithium-ion battery products of Comparative Example 1 and Examples 2-8 were also tested according to the above steps.

[0163] Table 3 Performance test results of secondary batteries prepared using the conductive pastes in Examples 1-8 Table 4 Performance test results of secondary batteries prepared using the conductive pastes from Comparative Examples 1-5 Based on the above results, it can be seen that Examples 1 to 8 have achieved good results in terms of wettability, adhesion, water resistance, crack resistance, conductivity, and battery capacity retention of the conductive coating.

[0164] First, the interfacial contact angles between the conductive paste and the aluminum foil are all less than 80°, with most falling between 60° and 70°. After being coated onto the aluminum foil surface, the conductive paste exhibits good wetting properties, spreading well on the foil surface. Furthermore, the interfacial contact angles between the conductive coating and water are also all less than 80°, with most falling between 60° and 70°. The conductive coating also demonstrates good wetting properties with the water-based positive electrode active material, allowing the material to spread well on the conductive coating.

[0165] Because this embodiment uses an aqueous binder, it can form good wetting between the aluminum foil and the aqueous positive electrode material, effectively improving the efficiency of conductive coating application, and also improving the strength and stability of the bond between the positive electrode active material and the conductive coating.

[0166] Furthermore, the peel force of the electrode sheets is greater than 50 N / M. A high peel force indicates that the conductive coating can firmly bond the positive electrode active material to the aluminum foil. After several cycles, the positive electrode active material can maintain a good connection with the aluminum foil, is not easy to delaminate, and can ensure the battery capacity.

[0167] In the embodiments of this application, the mass ratio R1 of the curing agent and the water-based adhesive used in the binder is within the range of 0.03 to 0.16. This is because when the amount of curing agent added is controlled within a reasonable range, the curing agent and the binder undergo a cross-linking reaction to obtain an appropriate degree of cross-linking. The resulting three-dimensional cross-linked network structure gives the conductive coating obtained from the conductive paste good water resistance. On the other hand, the binder molecules can still maintain good adhesion performance under an appropriate degree of cross-linking. Therefore, selecting the above-mentioned mass range for formulation is the optimal range to ensure both adhesion and water resistance.

[0168] Furthermore, the water resistance time of the electrode sheets all exceeded 180 seconds, and the conductive coating did not dissolve during the water resistance period. Wiping with lint-free paper did not cause the conductive coating to peel off. Figure 8 As shown, in Example 1, a good bond is formed between the positive electrode material layer 6 and the aluminum foil 7, without any gaps. The above results demonstrate that the electrode sheet in this application has good water resistance. Specifically, after the conductive coating is formed, it does not easily dissolve in water. When the conductive coating comes into contact with water in the positive electrode material, it still maintains good physicochemical properties, does not dissolve, and has strong adhesion.

[0169] In the embodiments of this application, a three-dimensional network structure is generated by the cross-linking reaction of the curing agent and the water-based binder, ensuring the water resistance of the conductive coating. Therefore, the active material in the positive electrode sheet can be firmly connected to the aluminum foil to ensure the capacity and cycle performance of the secondary battery.

[0170] Furthermore, the number of cold-pressed cracks was less than or equal to 1. This indicates that during the cold pressing process of the positive electrode sheet, the current collector surface and the conductive coating adhered tightly without gaps. Therefore, during pressing, the deformation between the positive electrode coating and the conductive coating was small, and the relative displacement was minimal, preventing the positive electrode coating from cracking. Conversely, if the conductive coating was dissolved or incompatible with the current collector surface, the adhesion between the two was weak or there were gaps, resulting in large deformation during pressing and causing the coating to deform and crack.

[0171] Furthermore, the resistance in Examples 1 to 8 is less than 0.7Ω.

[0172] In the embodiments of this application, since an appropriate amount of conductive agent is added to the conductive coating, good conductivity can be ensured, and good electrical energy conduction can be carried out between the positive electrode active material and the aluminum foil.

[0173] Furthermore, in Embodiments 1 to 8 of this application, an unexpected technical effect was achieved: the battery capacity retention rate of the secondary battery was further improved.

[0174] The applicant believes that, due to the excellent adhesion properties of the conductive coating to the active material and aluminum foil in Examples 1 to 8 of this application, the active material and aluminum foil can be better bonded together. This avoids the active material from detaching from the aluminum foil or the bonding being loose, which would reduce the contact area between the coatings, making electron transport difficult, increasing the electrode resistance, or causing various electrical performance abnormalities and capacity decay due to local insulation and effective material loss caused by coating detachment. Therefore, the above technical solution ensures the battery's capacity and safety, and improves the battery capacity retention rate. Of course, this beneficial effect is not limited to the above reasons. All technical effects achieved by the embodiments of this application are obtained through the technical means of this application and should fall within the protection scope of this application.

[0175] In contrast to the embodiments described above, no curing agent was added to the raw materials of the conductive paste in Comparative Example 1. Figure 9 The image shows a cross-section of the positive electrode sheet in Comparative Example 1 under an electron microscope. A noticeable gap is formed between the positive electrode material layer 8 and the aluminum foil 9 in Comparative Example 1. This is because no curing agent was added to the binder; therefore, it dissolves upon contact with the water-based positive electrode active material after drying. Experiments show that its water resistance time is only 10 seconds, after which the gap appears. This demonstrates that without adding a curing agent to the water-based binder, the water resistance effect of Examples 1-8 of this application cannot be achieved.

[0176] In Comparative Example 2, the adhesive used was styrene-butadiene rubber (SBR). The aluminum foil could not form a good wetting layer with the SBR, and the conductive paste in Comparative Example 2 could not be properly coated onto the aluminum foil. Therefore, the above embodiments could not effectively bond the positive electrode active material and the aluminum foil.

[0177] In Comparative Example 3, polyvinylidene fluoride was used as a binder. The aluminum foil could not form a good wetting with the polyvinylidene fluoride, and the conductive paste in Comparative Example 3 could not be coated on the aluminum foil. Therefore, the above embodiments could not effectively bond the positive electrode active material and the aluminum foil.

[0178] In Comparative Example 4, an oily solvent, N-methylpyrrolidone, was used. The above-mentioned material could not form good wettability with the aqueous positive electrode active material, and the positive electrode active material could not be coated on the conductive coating. Therefore, the above-mentioned embodiments could not effectively bond the positive electrode active material and the aluminum foil.

[0179] In Comparative Example 5, an oily solvent, N-methylpyrrolidone, was used. The above-mentioned material could not form good wettability with the aqueous positive electrode active material, and the positive electrode active material could not be coated on the conductive coating. Therefore, the above-mentioned embodiment could not effectively bond the positive electrode active material and the aluminum foil.

[0180] In summary, comparative examples 1 to 5 failed to effectively improve the adhesion and water resistance of the conductive coating.

[0181] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. A conductive paste, characterized in that, It includes the following raw material components: Waterborne adhesives, including waterborne polymers with polycarboxyl functionality; Conductive agent; Dispersants; and A curing agent is used for crosslinking with the aqueous polymer having polycarboxyl functionality, wherein the mass ratio of the curing agent to the aqueous adhesive is 0.03 to 0.

16.

2. The conductive paste according to claim 1, characterized in that, The conductive paste comprises, by weight parts: 100 parts of water-based adhesive 50-150 parts of conductive agent 800-850 parts of dispersant 3-16 parts of curing agent.

3. The conductive paste according to claim 1 or 2, characterized in that, The aqueous polymer with polycarboxyl functionality includes at least one of aqueous acrylic resin, ethylene-vinyl acetate copolymer, and acrylonitrile multi-component copolymer with polycarboxyl functionality.

4. The conductive paste according to claim 1 or 2, characterized in that, The waterborne acrylic resin includes copolymers of polyacrylic acid, acrylic acid, acrylates, and optionally other ethylene unsaturated monomers, or combinations thereof; optionally, the waterborne acrylic resin includes polyacrylic acid with a number average molecular weight of 300,000 to 800,000; optionally, the acrylic acid is partially neutralized to form a salt.

5. The conductive paste according to any one of claims 1 to 4, characterized in that, The curing agent comprises a compound having two or more carboxylic acid reactive functional groups, optionally, the carboxylic acid reactive functional groups being selected from at least one of aziridine, ethylene oxide, amino, and carbodiimide. Optionally, the curing agent includes at least one of aziridine functional compounds, polycarbodiimide and its salts, epoxy-functionalized silane compounds, polymers grafted with epoxy silanes, and polyethyleneimine. Optionally, the number average molecular weight of the polycarbodiimide is 10,000 to 40,000.

6. The conductive paste according to claim 2, characterized in that, The dispersant includes an aqueous solvent, and optionally, the aqueous solvent includes water.

7. The conductive paste according to any one of claims 1 to 4, characterized in that, The conductive paste also includes a thickener in its raw material components, which includes at least one of xanthan gum, carboxymethyl cellulose and its salts, or poly(N-vinylacetamide).

8. The conductive paste according to any one of claims 1 to 4, characterized in that, The conductive agent includes at least one of carbon black, graphite, acetylene black, Ketjen black, graphene, and carbon nanotubes.

9. A method for preparing the conductive paste according to any one of claims 1 to 8, characterized in that, The method includes: The conductive agent, the dispersant, and the aqueous binder are uniformly mixed to obtain a premix; The curing agent is added to the premix and mixed evenly to obtain the conductive paste.

10. A current collector, characterized in that, The invention includes a substrate and a conductive coating applied to the substrate, the conductive coating comprising a conductive agent and an aqueous polymer binder having polycarboxyl functionality, wherein the aqueous polymer is cross-linked to form a three-dimensional network structure.

11. The current collector according to claim 10, characterized in that, The conductive coating is formed by curing the conductive paste as described in any one of claims 1-8.

12. The current collector according to claim 10 or 11, characterized in that: The substrate includes aluminum foil or an aluminum-containing polymer composite.

13. The current collector according to claim 10 or 11, characterized in that: The peel force N between the conductive coating and the substrate is ≥50 N / M.

14. An electrode sheet, characterized in that, include: The current collector as described in any one of claims 10 to 13; An active material layer is disposed on the conductive coating of the current collector.

15. The electrode sheet according to claim 14, characterized in that, The active material layer comprises: a lithium phosphate with an olivine structure and an aqueous polymer binder.

16. A secondary battery, characterized in that, Including the positive electrode sheet as described in claim 14 or 15.

17. A battery module, characterized in that, Includes the secondary battery as described in claim 16.

18. A battery pack, characterized in that, Includes the battery module as described in claim 17.

19. An electrical appliance, characterized in that, It includes at least one selected from the secondary battery of claim 16, the battery module of claim 17, or the battery pack of claim 18.